การพัฒนาการจัดการเรียนการสอนด้านการสร้างเสริมสุขภาพเด็กวัยเรียนสำหรับครูสังกัดโรงเรียนตำรวจตระเวนชายแดน กองกำกับการตำรวจตระเวนชายแดนที่ 22 อุบลราชธานี - สาระรักษ์, มินตรา; หลาบคำ, จิราภรณ์; ทองดำ, สมเจตน์; ทิพย์พิลา, จีราพร; ศิริบูรณ์พิพัฒนา, จินตนา (Area Based Development Research Journal, 2016)
บทคัดย่อไม่สมบูรณ์ The development of health promoting learning plan of school-aged childern for teasher in Border Patrol Schools, Border Patrol Police Operation Division 22nd, Ubon Ratchatani province. The objective of this research was to develop of health promoting learning plan among school-aged children for teacher in Border Patrol Schools, Border Patrol Police Operation Division 22, Ubon Ratchatani province. Participants included teacher and administrator of 12 schools. The research was based on processes and activities that involved the enhancement of participation, learning and exchange between the research team and participants, a total of 53 people. Results of this study found that students had health problems, such as nutritional problem, caries, poor hygiene, and waste management in school was not in principle. All schools didn’t have health promoting learning plan that can be applicable for the benefit of students, school and community. The processes of participatory research enabled all schools to prepare health promoting learning plans or health projects for student, as well as waste management projects that can actually be implemented through the insertion of health promotion issues in these projects. The schools expected that these projects can be carried out continuously with students and their family. The issues of health promoting learning plans were 1) Nutritional solving for these overweight, slim, dwarf and shrub children. 2) Dental Care 3) National Health Commandments 4) Waste management problem in school.